Neuropsychiatric Aspects of Congenital Heart Disease: A Review of Current Literatures - Herick Alvenus Willim; Kartini RIta Sari; Nurfadella; Nurlia Desyanti (Biomedical Journal of Indonesia, 2021)
Congenital heart disease (CHD) is a structural abnormality in the heart or major intrathoracic blood vessel that is present at birth. Advances in modern medical science and technology have contributed to an increase in life expectancy and population of CHD patients. Survivors of CHD may not only experience complex medical problems due to sequelae or complications of the underlying CHD but may also experience neuropsychiatric disorders. This review article aims to provide an understanding of the neuropsychiatric aspects of CHD, including clini cal manifestations, risk factors and mechanisms, detection, and management of neuropsychiatric disorders in CHD. This review showed that CHD patients are prone to behavioral disorders, neurodevelopmental disorders, and mental health disorders such as anxie ty, depression, and post-traumatic stress disorder which can cause a decrease in quality of life. The risk factors and mechanisms of neuropsychiatric disorders in CHD are complex and multifactorial. Early detection and referral of neuropsychiatric disorders are important. Management requires a multidisciplinary team approach.